Phase Transitions and Formation of a Monolayer-Type Structure in Thin Oligothiophene Films: Exploration with a Combined In Situ X-ray Diffraction and Electrical Measurements - Eduard Mikayelyan; Linda Grodd; Viachaslau Ksianzou; Daniel Wesner; Alexander I. Rodygin; Holger Schönherr; Yuriy N. Luponosov; Sergei A. Ponomarenko; Dimitri A. Ivanov; Ullrich Pietsch; Souren Grigorian (Nanoscale Research Letters, 2019)
Abstract A combination of in situ electrical and grazing-incidence X-ray diffraction (GIXD) is a powerful tool for studies of correlations between the microstructure and charge transport in thin organic films. The information provided by such experimental approach can help optimizing the performance of the films as active layers of organic electronic devices. In this work, such combination of techniques was used to investigate the phase transitions in vacuum-deposited thin films of a common organic semiconductor dihexyl-quarterthiophene (DH4T). A transition from the initial highly crystalline phase to a mesophase was detected upon heating, while only a partial backward transition was observed upon cooling to room temperature. In situ electrical conductivity measurements revealed the impact of both transitions on charge transport. This is partly accounted for by the fact that the initial crystalline phase is characterized by inclination of molecules in the plane perpendicular to the π-π stacking direction, whereas the mesophase is built of molecules tilted in the direction of π-π stacking. Importantly, in addition to the two phases of DH4T characteristic of the bulk, a third interfacial substrate-stabilized monolayer-type phase was observed. The existence of such interfacial structure can have important implications for the charge mobility, being especially favorable for lateral two-dimensional charge transport in the organic field-effect transistors geometry.